Corporate taxes and the taxation of dividends - Williams, John Mark (Rhodes University, Faculty of Commerce, Department of Accounting, 1997)
The classical system of taxation, whereby companies are taxed without a deduction for dividends paid and shareholders are taxed on their dividend receipts, results in double taxation of dividends. Split rate and imputation systems have been developed in an attempt to mitigate the effects of double taxation of dividends. Double taxation of dividends and differences between corporate and maximum individual marginal tax rates result in corporate tax systems lacking neutrality. Distortions arise between organisational forms, between debt and equity financing and between the retention and distribution of profits. Various methods of integrating corporate and individual taxes have been advocated to overcome the lack of neutrality caused by corporate taxes. Following the introduction of the South African Income Tax Act in 1914, a number of taxes relating to dividends have existed. These have included a Dividend Tax, Non-resident Shareholder's Tax, Undistributed Profits Tax and Secondary Tax on Companies, hereafter referred to as STC. STC is a tax on net dividends declared and results in distributed income being taxed at higher rates than retained income. Despite the implementation of group relief provisions, STC results in an inhibition on the reinvestment of profits within the context of a group of companies. It is also a major cause of the lack of neutrality of the South African corporate tax system. As a result of the lack of neutrality and inhibition of group reinvestment caused by STC, a full imputation system is suggested as an alternative to replace STC.
Keywords: Uncatalogued